Evolução diurna e anual da frequência das coberturas de céu em Botucatu/SP - Teramoto, Érico Tadao [UNESP] (2012)
This work presents an analysis of the pattern variation of the sky conditions in Botucatu/SP. The classification was based on the clarness index KT. It was used in the classification a database of global solar irradiance in the horizontal, measured at Radiometric Station of UNESP in Botucatu (latitude 22.85°S, longitude 48.43°W, altitude 786 m) from 1996 to 2005. We analyzed the variations in frequency, during the photoperiod and over the year, of the sky conditions: I - Cloudy (KT < 0.35); II - party cloudy with dominance for the diffuse (0.35 < 0.55 < KT)) III - party cloudy with dominance for the clear (0.55 < KT < 0.65) and IV - clear (KT > 0.65). The frequency of sky conditions I and II are higher during the rainy season of the year and in hours close to sunrise and sunset. And it is lower during the dry season an in hours near noon, in wich there is a predominance of sky conditions III and IV. The monthly hourly frequency of sky condition I ranged from 46,91% of the photoperiod in January to 25.27% in August. And the frequency monthly daily ranged from nine days in January to three days in August. To the sky condition IV, the frequency monthly hourly ranged from 38.81% of the photoperiod in August to 18.17% im January. And the frequency monthly daily ranged from 17 days in August to three days in January.